Designing Low Impedance Interface Films Simultaneously on Anode and Cathode for High Energy Batteries. Issue 22 (29th May 2018) - Liao, Bo; Li, Hongying; Xu, Mengqing; Xing, Lidan; Liao, Youhao; Ren, Xiubin; Fan, Weizhen; Yu, Le; Xu, Kang; Li, Weishan
Abstract: High energy batteries urgently required to power electric vehicles are restricted by a number of challenges, one of which is the sluggish kinetics of cell reactions under low temperatures. A novel approach is reported to improve the low temperature performance of high energy batteries through rational construction of low impedance anode and cathode interface films. Such films are simultaneously formed on both electrodes via the reduction and oxidation of a salt, lithium difluorobis(oxalato) phosphate. The formation mechanisms of these interface films and their contributions to the improved low temperature performances of high energy batteries are demonstrated using various physical and electrochemical techniques on a graphite/LiNi0.5 Co0.2 Mn0.3 O2 battery using 1m LiPF6 ‐ethylene carbonate/ethyl methyl carbonate (1/2, in weight) baseline electrolyte. It is found that the interface impedances, especially the one on the anode, constitute the main obstacle to capacity delivery of high energy batteries at low temperatures, while the salt containing fluorine and oxalate substructures used as additives can effectively suppress them. Abstract : High energy batteries suffer from low performance at low temperatures due to large interface impedance of electrolyte decomposition products mainly consisting of poor ionically conductive polycarbonates and LiF, especially on the anode. This issue can be solved by constructing interface films simultaneously on the anode and cathode with lithium salts as an electrolyte additive, which can be reduced or oxidized preferentially compared to a baseline electrolyte.